The future of fog - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
If water does not fall from the sky, scoop it out of the air, at least in areas where dew and fog occur regularly and other water resources are scarce. There are several small fog collecting programmes in countries such as the Dominican Republic,...